Projetos esportivos no enfrentamento dos determinantes sociais na vida de crianças e adolescentes vulneráveis - Felício, Carlos Henrique Vieira (2022)
In the last accesses, there was a significant increase in investments in social projects for children and linked to sport and physical activity, in the search to reduce the indicators that are unfavorable to health, given the IBGE data in 2018, indicate the low of and adolescents to any type of leisure and culture, the index of social inequalities, with sport being a right acquired by the 1988 Constitution. The implementation of children in social sports projects is a strategy that the State is using as a public policy proposal, in of health determinants to reduce social risk, encouraging a healthy lifestyle. Social tools use sport as educational, through the values that sport provides, such as companionship, solidarity, respect for others and rules, and others, many indirectly experience, without understanding that vulnerability does not necessarily indicate a research situation million, but the situation of establishing new vulnerabilities, and data from Unicef (2021), represent that currently children and adolescents, 53.77 of the data justify the concern of this concern. This study aimed to investigate the practice of sport as a strategy to face social determinants in the lives of 45 vulnerable adolescent children in a universe of 390, developed in 3 cities in the interior of São Paulo, Brazil., benefited by the São Paulo Sports Incentive Law, based on the Model of Social Determination of Health, adapted by Dahlgren and Saúde (1991 with great concern for a healthy lifestyle and strengthening of the Whitehead – family model). This is field research with a quantitative-qualitative, exploratory and cross-sectional design. In this way, data obtained was used to characterize the profile of the research participants through structured and semi-structured individual interviews, and the focus group technique, with questions that involve the perception of sports practice related to behavior change in the school context, family and social life, and quality of life. The results were systematized in tables, graphs, transcriptions of the speeches were carried out for content analysis. As a result, it is highlighted that sport plays an important role in the lives of children and adolescents, which is positive and true. The study offered a new look, with another perspective of the impact of physical activity in the dimension of health promotion and in facing the social issue, in the quality of life and health promotion. The study indicates that social projects contribute to the continuing education of children and adolescents, with changes in daily behavior, habits and customs, effectively contributing to the integral formation of students, with values that will accompany them throughout their lives. However, participation in effective sports programs not only promotes the improvement of physical status, but also changes in the behavior of those involved, which, when associated with other factors, play an important role in human development. Social sports projects seek to improve the quality of life of children and adolescents, contributing to a healthy lifestyle, helping vulnerable families to face social risk. Keywords: Education. Health Promotion. Public policy